Od transfromacji do integracji: wybrane uwagi nt. “bezpośredniej” partycypacji obywateli w procesie podejmowania decyzji politycznych po 1989 r. na przykładzie państw Grupy Wyszehradzkiej - Musiał-Karg, Magdalena; Lesiewicz, Elżbieta (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2014)
The subject of this paper concerns selected experiences of citizens from the Visegrad Group countries (Poland, the Czech Republic, Slovakia and Hungary) participating in the process of ‘direct’ (that is, exercised by means of the tools of direct democracy) decision making as regards the most important matters, ranging from those related to the process of political transformation to the decision on accession to the European Union. The present considerations dwell on the experiences of Central and East European countries.
Keywords: partycypacja; transformacja; transformacja po 1989; integracja; partycypacja polityczna